KARAKTERISTIK KIMIA PUPUK ORGANIK CAIR DARI TIGA JENIS KOTORAN HEWAN DAN KOMBINASINYA - Nova D. Lussy; Lena Walunguru; Kristofel H. Hambamarak (Partner, 2017)
The purpose of this study is to determine the chemical characteristics of the liquid organic fertilizer from several types of animal manures. The research had been conducted in the experimental garden site of Department of Food Crops and Horticulture, Kupang State Agricultural Polytechnic. The research was designed using a simple statistical l with 7 treatments which were liquid organic fertilizer (LOF) made from cow manure; LOF made from chicken manure; LOF made from goat manure; LOF made from goat and cow manure; LOF made from chicken and cow manure; LOF made from chicken and goat manure; and LOF made from goat, cow and chicken manure. The observed parameters were C/N, pH, macro nutrient and micro nutrient contents. The results showed that the liquid organic fertilizer made from manure of cow, chicken, goat, and its combination of these materials can be applied to cultivation plants but have not met the minimum technical requirements of organic liquid fertilizer (Minister of Agriculture Regulation No.70/Permentan/SR.140/10/2011). The best result was showed by the LOF made from chicken manure with pH 7.32 , N 1619.68 ppm , 541.44 ppm P, K 4000.00 me/100g , Zn 14.43 me/100g , Cu 4.33 me/100g. The highest C/N was found in LOF made from goat and cow manure which was 0.66. The highest Mg was in the LOF made from cow, goat and chicken manure for 723.10 me/100g. The highest Ca was in LOF made from goat manure. The highest S was in the LOF made from goat and cow manure for 749.95 me/100gÂ  while the Fe and Mn were highest found in the LOF made from cow manure which was equal to 84.02 ppm and 23.05 me/100g.Â Keywords : LOF, Fertilizers, Characteristic, Animal manure.